Technology, law and the working environment - Ashford, Nicholas Askounes; Caldart, Charles C. (Van Nostrand Reinhold, 1991)
"Ashford and Caldart examine the legal issues associated with technology-related workplace problems, discussing such matters as occupational health and safety, toxic-substance regulations, and right-to-know requirements."